Periodontitis links to concurrent metabolic disorders and abnormal liver function in pregnant women - Zhang, Feng; Zhao, Dan; Xu, Xiaoyi; Wen, Ping; Li, Huijun; Yu, Rong; Cheng, Tianfan; Zheng, Zheng; Yang, Hong; Yang, Chuanzhong; Yao, Jilong; Jin, Lijian (Oral diseases, 2024)
Objective This cross‐sectional study investigated the association of periodontitis with the metabolic status and hepatic function in pregnant women. Materials and Methods Full‐mouth periodontal conditions, metabolic profiles, and hepatic function were assessed in 219 self‐reported healthy pregnant females. The association of periodontal status with the systemic parameters was evaluated by parametric and non‐parametric tests, and multivariate logistic regression analysis. Results Overall, periodontal status was positively associated with the metabolic profiles and hepatic function test results. The subjects with periodontitis exhibited higher levels of body mass index (BMI) (p < 0.01) and serum aspartate transaminase (AST) (p < 0.05), elevated diastolic blood pressure (DBP) (p < 0.05), and lower levels of high‐density lipoprotein cholesterol (p < 0.05) than those of the counterparts. The periodontitis severity was strongly correlated with BMI and AST levels, and the extent of periodontal inflammation was related to DBP (p < 0.01). The periodontitis patients at 34–36 gestational weeks showed higher blood pressure and AST levels than those of non‐periodontitis subjects (p < 0.05). Conclusion Our findings on the notable links of periodontitis to concurrent metabolic disorders and abnormal liver function in pregnant women highlight the need of proactive integration of regular periodontal screening and healthcare in maternal programs for promoting optimal health and wellbeing of mothers‐to‐be and newborns.